Jati Kasilih ku Janti Values in Intergenerational Cultural Communication at Urban Kampung - Muslim Muslim; Muhammad Reza; Ratih Siti Aminah; Jordy Satria Widodo; Yuyus Rustandi; Andi Chairunnas (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study investigates how the Sundanese philosophical principle Jati Kasilih ku Janti is transmitted across generational boundaries through cultural communication in the urban kampung community of Kampung Labirin, Bogor City. The research examines (1) the specific cultural communication channels through which the principle is transmitted across three generational cohorts; (2) intergenerational communication gaps and the adaptive strategies employed to bridge them; and (3) a theoretical model of intergenerational cultural value transmission grounded in the empirical findings. A qualitative approach employing ethnography of communication was used, with data from nine months of participatory observation, in-depth interviews with 22 informants across three generational cohorts (Generation I: 1940–1964; Generation II: 1965–1989; Generation III: 1990–2006), and two focus group discussions. Three dominant transmission channels were identified: oral storytelling (ngawangkong), ritual enactment (upacara adat), and embodied cultural practice (pembiasaan budaya). Significant intergenerational communication gaps were documented alongside effective adaptive bridging strategies including media hybridization and facilitated dialogue. The Five-Stage Intergenerational Value Transmission Model (IVTM-5) is proposed, comprising Encoding, Channeling, Decoding, Negotiation, and Re-encoding stages. This model contributes to Indonesian-specific cultural communication theory and provides practical guidance for urban cultural preservation programs.